ANALISIS MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DINAS MASYARAKAT KARAWANG - Akmal Khairi Sudrajat; Syifa Pramudita Faddilla (Jurnal Pijar, 2023)
This research aims to find out the performance assessment system, as well as related factors in improving the performance of employees in the Community Empowerment Office and Karawang Regency Village. This study uses descriptive methods with data collection techniques in the form of interviews and observations. The results of this study are in conducting data on employee performance, the Community Empowerment Office and Karawang Regency Village using a system called PARE (Performance Agreetment Report by Electronic). As for improving performance, a leader with employees must have a good communication relationship, so that it can increase employee motivation and morale, and can foster work discipline. This aimed to found factors which influence employee’s performance of Commerce and Industrial Affairs Department Karawang. Those factors were motivation and work environment. Employees who have high work motivation will give positive effect for organization, therefore organization purpose reached. Hypothesis examination carries out by spreads questionnaire about 74 employees of service Karawang